The pharmacological management of erectile dysfunction – Update 2016 - André Marais (South African Family Practice)
Erectile dysfunction (ED) is a trivial condition with a prevailing incidence worldwide. Phosphodiesterase-5 inhibitors (PDE-5) have revolutionised the treatment of ED and are regarded as one of the most successful drug groups in modern medicine. Generally PDE-5 inhibitors are well tolerated and the incidence of side-effects is low, however a small percentage of individuals experience headache, flushing and abdominal discomfort, resulting in discontinuation of therapy. This has led to the development of second generation PDE-5 inhibitors, displaying more selectivity for the PDE-5 enzyme thereby reducing treatment interruption and improving compliance. Several other treatment modalities, including testosterone replacement therapy and prostaglandin administration are available for resistant or failed first-line treatment. This review provides an update on the current, and future, available drugs used in the management of ED.